2003
DOI: 10.4310/mrl.2003.v10.n6.a7
|View full text |Cite
|
Sign up to set email alerts
|

Structure theorem for compact Vaisman manifolds

Abstract: Abstract. A locally conformally Kähler (l.c.K.) manifold is a complex manifold admitting a Kähler coveringM , with each deck transformation acting by Kähler homotheties. A compact l.c.K. manifold is Vaisman if it admits a holomorphic flow acting by non-trivial homotheties onM . We prove a structure theorem for compact Vaisman manifolds. Every compact Vaisman manifold M is fibered over a circle, the fibers are Sasakian, the fibration is locally trivial, and M is reconstructed from the Sasakian structure on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 7 publications
0
70
0
1
Order By: Relevance
“…If C(W min ) Z → M is the covering given by the minimal presentation of a compact Vaisman manifold and π the projection of the cone onto its radius, it is easy to check that π is equivariant with respect to the action of the covering maps on C(W min ) and the action of n ∈ Z on t ∈ R given by n + t. This describes in an alternative way the projection over S 1 of the Structure Theorem in [OV03], and moreover provides a structure theorem for other types of locally conformal structures, where the compactness of the base of the cone is given by other ways (see [IPP05] for an application to G 2 , Spin(7) and Spin(9) structures).…”
Section: Theorem 55 the Action Of A Connected Group G On A Compact mentioning
confidence: 99%
See 2 more Smart Citations
“…If C(W min ) Z → M is the covering given by the minimal presentation of a compact Vaisman manifold and π the projection of the cone onto its radius, it is easy to check that π is equivariant with respect to the action of the covering maps on C(W min ) and the action of n ∈ Z on t ∈ R given by n + t. This describes in an alternative way the projection over S 1 of the Structure Theorem in [OV03], and moreover provides a structure theorem for other types of locally conformal structures, where the compactness of the base of the cone is given by other ways (see [IPP05] for an application to G 2 , Spin(7) and Spin(9) structures).…”
Section: Theorem 55 the Action Of A Connected Group G On A Compact mentioning
confidence: 99%
“…The main tool to prove the equivalence is the following Theorem, together with the Structure Theorem in [OV03].…”
Section: Vaisman Automorphisms and Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 5.2. The above result is an extension of [OV2], where the triviality of the adapted cohomology is derived directly from the structure theorem of compact Vaisman manifold [OV1]. For the general case of Riemannian foliations a similar attempt is not a trivial extension, as structural aspects of Riemannian foliations should be also considered [Mo].…”
Section: Corollary 54 For Any Vaisman Foliationmentioning
confidence: 99%
“…Note that Boyer and Galicki discussed a similar problem in Section 8.2 of [8]. The product of S 1 with a Sasakian manifold admits geometric structures called a Vaisman manifold or a locally conformal Kähler manifold (see Ornea and Verbitsky [37]). Belgun [5] showed that both of structures are not stable under small deformations of complex structures.…”
mentioning
confidence: 99%